2018
DOI: 10.1136/annrheumdis-2018-213585
|View full text |Cite
|
Sign up to set email alerts
|

2018 EULAR recommendations for physical activity in people with inflammatory arthritis and osteoarthritis

Abstract: Regular physical activity (PA) is increasingly promoted for people with rheumatic and musculoskeletal diseases as well as the general population. We evaluated if the public health recommendations for PA are applicable for people with inflammatory arthritis (iA; Rheumatoid Arthritis and Spondyloarthritis) and osteoarthritis (hip/knee OA) in order to develop evidence-based recommendations for advice and guidance on PA in clinical practice. The EULAR standardised operating procedures for the development of recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
433
1
40

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(483 citation statements)
references
References 112 publications
9
433
1
40
Order By: Relevance
“…However, compelling evidence shows that disuse actually leads to joint destruction, muscle weakness and atrophy, causing reduced physical function 2,3 . Such evidence has led to the contemporary abrogation of the 'bed rest paradigm' for rheumatic diseases and has guided new approaches to clinical practice that emphasize physical activity as an important part of therapy to improve patients' symptoms 7 . Given that physical inactivity and sedentary behaviour will potentially increase as a function of social distancing measures during the COVID-19 pandemic, patients with rheumatic diseases who are already hypoactive might be at particular risk of worsened disease activity and symptoms, general comorbidities and poor quality of life (Fig.…”
mentioning
confidence: 99%
“…However, compelling evidence shows that disuse actually leads to joint destruction, muscle weakness and atrophy, causing reduced physical function 2,3 . Such evidence has led to the contemporary abrogation of the 'bed rest paradigm' for rheumatic diseases and has guided new approaches to clinical practice that emphasize physical activity as an important part of therapy to improve patients' symptoms 7 . Given that physical inactivity and sedentary behaviour will potentially increase as a function of social distancing measures during the COVID-19 pandemic, patients with rheumatic diseases who are already hypoactive might be at particular risk of worsened disease activity and symptoms, general comorbidities and poor quality of life (Fig.…”
mentioning
confidence: 99%
“…Even so, the disease activity measurements were performed by different trained evaluators who were unaware of the specific therapeutic regimen to make the study more objective. Second, previous studies demonstrated that metabolic factors, including dietary intake and physical activity, were associated with the occurrence and disease activity [34][35][36] . However, as the setup of the parameters was mainly focused on the change in RA disease activity before and after treatment, data on these metabolic factors were not collected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Altering the intervention in response to patient's pain levels improved completion rates of the intervention. Conclusion: When designing PA programs for people with RA, the EULAR PA guidelines for people who have inflammatory arthritis [3] should be followed. However, it should be noted that engagement and participation in PA interventions is increased when the intervention is of low impact PA and starts at a low-moderate intensity.…”
Section: Referencesmentioning
confidence: 99%
“…The Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety and depression levels. Biopsychosocial status of the patients was evaluated by the BETY-Biopsychosocial Questionnaire (BETY-BQ) (2,3). The same evaluations were repeated after 3 months in 36 patients using anti-TNF.…”
mentioning
confidence: 99%